Numeric simulation and experimental validation for a Novel Trapezoidal Solar Collector - Salvo, Aien Weni (2024)
In a global warming context, the diversification of the energy matrix is essential for mitigation. Solar devices have begun to play an important role in this sense, flat-plate solar collectors being the most practical device. On the other hand, numerical modeling and experimental validation are important tools for improving the performance of these technologies. In this work, a trapezoidal solar air heating collector for food drying processes was modeled by using the Simusol open-access software, and experimental validation was performed. This particular shape presents a geometrical novelty since no other similar designs were found in the available literature, even in such an application as food drying. Key parameters, such as air temperature, global efficiency, air mass flow, global heat loss coefficient, and useful heat, are determined and discussed. The proposed air collector numerically behaves as expected. The output air temperature reaches about 100 °C, while the peak heat gain is about 900 W, which makes the air heating collector suitable for drying applications. Due to natural convection being the main heat transferring mechanism, low air mass flows were obtained. For the case analyzed here, this last parameter ranges from 0.012–0.016 kg/s for the optimal thermal behavior. The numerical model developed is a reliable tool for designing thermal technologies without extra capital cost; the increase of collecting area leads to a considerable increase in the thermal power output and improves the psychrometric conditions of heated air.